Heavy Metal Content in Breast Milk and Contributing Environmental and Maternal Factors: A Systematic Review - Aisyiah, Aisyiah; Rahfiludin, Mohammad Zen; Agushybana, Farid; Sutiningsih, Dwi (Poltekkes Kemenkes Palu, 2025)
Background: Breast milk is an important source of nutrition for the growth and development of infants. It is highly susceptible to the accumulation of lipophilic compounds such as heavy metals. Breast milk can become a route through which infants are exposed to toxic substances like heavy metals. This study aimed to identify variations of trace elements and their associated factors contributing to the existence of trace elements in breast milk. Methods: This research employed a systematic literature review methodology utilizing PubMed, Scopus, and Science Direct databases. The search strategy followed specific English keywords to align with the PRISMA Extension for Systematic Reviews guidelines. Data synthesis involved a narrative approach, summarizing the main findings and interventions outlined in the chosen studies. The included articles consisted of full-text primary research published between 2013 and 2023. To mitigate potential language bias, only publications in English were considered for inclusion. Results: Our systematic review, comprising nine articles, revealed the presence of toxic metals including lead (Pb), cadmium (Cd), aluminum (Al), copper (Cu), chromium (Cr), mercury (Hg), and arsenic in human milk. Associated factors contributing to this presence include food intake (such as seafood, fruit, and canned fruit), water and canned drink consumption, smoking and exposure to smoke, regional location, and medical conditions. Conclusion: Heavy metals, including lead, cadmium, aluminum, copper, chromium, mercury, and arsenic are present in breast milk, influenced by factors like diet, water consumption, smoking, regional zones, and medical conditions. These findings underscore the urgent need for public health policies to monitor environmental exposure in lactating mothers and to develop dietary guidelines minimizing toxic exposure.